Characterization and Antimicrobial Activity of Chitosan Extracted from Squid Pen Wastes - Nur Nadhirah Adibah Mohd Nor Naser; Maryam Mohamed Rehan; Muhamad Arif Mohamad Jamali; Salina Mat Radzi (Malaysian Institute of Chemistry, 2024)
Indexed by Scopus